(untitled) (Ottawwa, Canada, 1997)
East Asian Integration: Synergies between firm strategies and goverment policies; Singapore advanced production base and smart hub of the electronics industry; ....
Keywords: International business enterprises,Doanh nghiệp kinh doanh quốc tế; Đông Á; East Asia